2011
DOI: 10.3399/bjgp11x588411
|View full text |Cite
|
Sign up to set email alerts
|

Activity Increase Despite Arthritis (AÏDA): phase II randomised controlled trial of an active management booklet for hip and knee osteoarthritis in primary care

Abstract: BackgroundThe Hip & Knee Book: Helping you cope with osteoarthritis was developed to change disadvantageous beliefs and encourage physical activity in people with hip or knee osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…Although some research has demonstrated it is possible to increase physical activity levels in those with chronic LBP [49] or OA [50,52], an understanding of which components are effective, i.e. the ‘active ingredients’ is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Although some research has demonstrated it is possible to increase physical activity levels in those with chronic LBP [49] or OA [50,52], an understanding of which components are effective, i.e. the ‘active ingredients’ is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The two papers reported in this issue of the Journal 5,6 point to an expanding evidence base that rejects the idea that primary care for osteoarthritis is about waiting until it is time to refer for a joint replacement. Not only are there simple positive approaches to reduce joint pain and disability in older people, but joint replacements, valuable and important as they are, will not be needed or wanted by everyone with osteoarthritis, and remain in need of a better evidence base to clarify optimal patient selection and timing of surgery.…”
Section: The Question Of When To Refermentioning
confidence: 99%
“…Results of their proofof-principle study suggest that a large trial to investigate this question would be feasible, but that any benefits in terms of extra numbers starting and maintaining exercise are likely to be modest, and that ways to repeat or reinforce advice over time need to be tested. 6 Why is it important, as Williams et al propose, to pursue the investigation of such small effects? One answer relates to GPs' responsibility for their population as well as their concern to help the individual.…”
Section: The Question Of Exercisementioning
confidence: 99%
See 2 more Smart Citations